The Role of the Malay Customary Institution in Off-Court Divorce Mediation: A Case Study in Rantau Pandan, Jambi - Azwar, Zainal; Firdaus, Firdaus; Nafis, Muhammad (Al-Risalah, 2020)
In general, the concept of mediation in fiqh literature concerns merely with pre-divorce conflicts. In contrast, the Malay Customary Institution in Rantau Pandan, Jambi also concerns with restoring household integrity after divorce. This paper aims at describing and analyzing the role of the Malay Customary Institution in restoring post-divorce households in Rantau Pandan. The field research was conducted where the data taken from in-depth interviews and documentation. This paper concludes that there are two forms of mediation process practiced by the Malay Customary Institution in Rantau Pandan: the mediation that is prompted by the initial request of the involving parties and that is without the precondition of reconciliation. The success of the Customary Institution in mediating familial conflicts is supported by several factors, such as; the competence of the mediators, kinship relations, and the goodwill of the respective parties. The mediation practiced of the Customary Institution works in line with the guidance of the Qurâ€™Än and the principle of mediation in Islam. Additionally, this institution has developed the concept of mediation outside the court, both in terms of form and task.